Hunting a ‘good life’: young lifestyle migrants in Finnish Lapland - Adams Ria-Maria (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (Polar Geography, 2023)
The abstract is available here: https://uscholar.univie.ac.at/o:1953411 The abstract is available here: https://uscholar.univie.ac.at/o:1953411